Summer tropical Atlantic drives autumn North American Arctic warming through western Pacific Bridge - Wei Lou; Cheng Sun; Jianping Li (Environmental Research Letters)
The Arctic climate system exhibits dramatic changes in autumn, yet its connection to the tropics remains unclear. This study leverages inter-basin/region teleconnectivity (IB(R)T) analysis to unveil the key teleconnected regions responsible for the connection between autumn Arctic temperature and tropical sea surface temperature (SST). A robust positive correlation is identified between North American Arctic (NAA) temperatures and North Tropical Atlantic (NTA) SST, with the NTA SST leading by one season. Observational evidence reveals that western Pacific (WP) subtropical high (WPSH) and SST play an intermediary role in this cross-seasonal tropical-Arctic connection. Summertime NTA warming triggers an intensification of the WPSH, subsequently inducing autumnal warming of WP SST via inter-basin interactions. This intensified WP convection generates a Rossby wave train propagating from the Northern WP eastward towards the NAA, ultimately leading to an anomalous high over the NAA. The increased atmospheric thickness and air temperature enhances downward longwave radiation, further contributing to surface warming over the NAA. The linear baroclinic model experiments, forced with thermal anomalies corresponding to WP SST warming, successfully reproduce the observed atmospheric circulation response and the associated air temperature changes over the NAA. Our findings provide insights into the role of inter-basin connections in Tropical-Arctic linkages.